Post-exercise Heart Rate Variability: Whole-body Cryotherapy vs. Contrast Water Therapy - Sautillet, Benoît; Leprêtre, Pierre Marie; Schmitt, Laurent; Ahmaidi, Said; Costalat, Guillaume (International Journal of Sports Medicine, 2021)
High-intensity training sessions are known to alter cardiac autonomic modulation. The purpose of this study was to compare the effects of whole-body cryotherapy, contrast water therapy and passive recovery on the time course of cardiac autonomic markers following a standardized HIT session. Eleven runners completed a high intensity session followed by one of the following recovery interventions: whole-body cryotherapy, contrast water therapy or passive recovery. Changes in cardiac autonomic modulation were assessed in supine and standing positions during an active tilt test at pre-, post-14 h and post-38 h. In supine, high-frequency power increased from pre- to post-14 h following whole-body cryotherapy (1661.1±914.5 vs. 2799.0±948.4 ms2, respectively; p=0.023) and contrast water therapy (1906.1±1327.9 vs. 4174.3±2762.9 ms2, respectively; p=0.004) whereas high frequency power decreased in response to passive recovery (p=0.009). In standing, low-frequency power increased from pre-to post-38 h (1784.3 ± 953.7 vs. 3339.8±1862.7 ms2, respectively; p=0.017) leading to an increase in total power from pre- to post-38 h (1990.8 ± 1089.4 vs. 3606.1±1992.0 ms2, respectively; p=0.017). Spectral analysis revealed that contrast water therapy appears to be a more efficient recovery strategy than whole-body cryotherapy in restoring cardiac autonomic homeostasis.
Keywords: recovery strategy; cryotherapy; contrast water therapy; cardiac autonomic homeostasis